Pembangunan Perdesaan Berkelanjutan di Desa Adat Osing, Kabupaten Banyuwangi: Sebuah Perspektif dari Pendekatan Penghidupan Berkelanjutan - Herman Cahyo Diartho; Fajar Wahyu Prianto; Amalia Fakhrun Nisa (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Sustainable development balances economic growth, social inclusion, and environmental preservation to promote long-term community welfare. This study examines rural development in Osing Traditional Village, Banyuwangi Regency, using the Sustainable Livelihood Approach (SLA) to identify key assets, vulnerabilities, and sustainability strategies. Employing a quantitative descriptive method, the study integrates pentagonal asset analysis, vulnerability assessment, and SWOT analysis with data collected through surveys and interviews. Findings reveal that natural capital is the dominant asset (value: 9.75), supported by social and physical capital. However, vulnerabilities such as fertilizer scarcity, rising input costs, and agricultural land conversion pose significant threats to sustainability. This study addresses a critical research gap by analyzing asset interactions in a rapidly transforming, tourism-dependent village, offering novel insights into the integration of cultural preservation, economic development, and risk mitigation. Beyond the case study, it contributes to the theoretical discourse on sustainable rural development and provides actionable policy recommendations. These include agricultural land protection, improved financial access, and community-driven initiatives to ensure long-term prosperity without compromising ecological integrity.